Pengaruh rasio keuangan daerah, pendapatan asli daerah (pad), dan dana alokasi umum (dau) terhadap alokasi belanja modal pada kabupaten/kota di provinsi riau tahun 2009-2012 - Fitri, Vella Kurniasih; Rasuli, Muhammad; Silfi, Alfiati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This research is aimed to analyze the influence of Local Government Measurement Ratio toward the Capital Expenditure for Public Services.The samples which are use in this research are regency/municipality of Riau province that report routine the realization report of the estimate income of regional expense (APBD) from 2009 until 2012 for Dirjen Perimbangan Keuangan Pemerintah Daerah(www.djpkpd.go.id). The sampling method used in this study is the sample selection aims (purposive sampling method). The stastical method used to test the research hypothesis is multiple regression using SPSS 18 software.The results of this research show that The Autonomy rate has negative influence toward the capital expenditure for public service. The effectiveness rate has positive influence toward capital expenditure for public service. The efficiency rate has negative influence toward capital expenditure for public service. Fund Local Own Revenue (PAD) has positive influence toward capital expenditure for public service , and the General Allocation Fund (DAU) have a significant effect on the Capital Expenditure for public serviceKey Word : autonomy ratio, effectiveness rate, efficiency rate, Fund Local Own Revenue, General Allocation Fund, capital expenditure.